History of Natural Disasters in Central Asia and Their Consequences - Tursunboyeva Maxsuda (Zien Journals, 2022)
Dangerous geological emergencies are as follows, according to resolution 455 of the Cabinet of Ministers: - earthquake, power, mountain threshing, sinking of the earth's surface . Hazardous geological processes and events play a special role in the occurrence of disasters, emergency situations, so the causes of dangerous geological poles, the laws of space distribution, the laws of space distribution, and various measures will be developed to protect people and public administration from catastrophic consequences. How to legally implement this problem
Keywords: implement; developed; measures; administration